Recent progress in formate dehydrogenase (FDH) as a non-photosynthetic CO2 utilizing enzyme: A short review. Issue 42 (December 2020) - Moon, Myounghoon; Park, Gwon Woo; Lee, Joon-pyo; Lee, Jin-Suk; Min, Kyoungseon
Highlights: Formate dehydrogenase interconverting CO2 and formate reversibly as CO2 reductase. NAD + -linked/metal (either Mo- or W-) containing FDHs are electroactive. Electroenzymatic system for producing formate from CO2 . Some FDHs are able to produce formate combined with hydydrogenase-driven H2 oxidation. Multi-enzyme cascade reaction combined with cofactor regeneration. Abstract: Formate dehydrogenase (FDH) has been considered as a nearly irreversible biocatalyst for catalyzing formate oxidation to CO2 for a long time. However, recent research clearly proved that certain FDHs, mainly NAD + -linked/metal (either W- or Mo-) containing enzymes, are capable of reversibly interconverting CO2 and formate, thereby having a significant role as a non-photosynthetic CO2 utilizing enzyme. We, herein, summarize and discuss not only recently discovered CO2 reduction activities and structure-based enzyme engineering reinforcing the CO2 reduction activity but also applications for a CO2 refinery including electroenzymatic approaches, whole-cell biocatalytic systems, and multi-enzyme cascade reactions in detail. Especially, this review concentrates on as well as comprehensively discusses recent progress. Furthermore, innovative results discussed herein might provide revelaratory insights applicable for constructing a feasible CO2 refinery system that utilizes CO2 as an abundant, cheap, and sustainable feedstock in order to produce value-added fuels and chemicals.